Variation in Soil Physicochemical Property of Oak Forests in Garhwal Himalaya - Mahato, Subhasis; Dasgupta, Sabyasachi; Todaria, N.P. (Indian Forester, 2025)
Quercus leucotrichophora (banj oak) predominates the mid-altitude temperate forests of the western Himalayas, serving as a keystone species that underpins both ecological stability and rural livelihoods. This study meticulously examines the impact of forest size and management practices on the physicochemical properties of soil within oak-dominated forests of the Garhwal Himalaya, Uttarakhand. Four sites—comprising two large reserve forests, one diminutive reserve forest, and one small community managed forest—were meticulously selected across the Pauri and Rudraprayag districts. Soil samples were taken from five distinct depths (0–100 cm) and subjected to analyses for moisture content, bulk density (BD), soil organic carbon (SOC), texture, water holding capacity (WHC), and pH. Rigorous statistical analyses, including ANOVA, Tukey’s HSD, correlation matrices, and Principal Component Analysis (PCA), unveiled significant disparities in soil parameters across both sites and depths. These findings illuminate the significance of forest size and management in regulating soil health, hydrological balance, and carbon sequestration, thereby offering critical insights for sustainable forest conservation and climate resilience within Himalayan ecosystems. The present study illustrates that reserve forests are more effective in regulating soil organic carbon as an ecosystem service than their smaller community-managed counterparts.